Negotiation of Symbolic Meaning in Visual-Participatory Catechesis Using YOUCAT for Kids: Perspectives of Symbolic Interactionism and Faith Development Dayak Children in Palangka Raya - Elia Karisma; Fransiskus Janu Hamu; Agnes Angi Dian Winei (Kirana Publisher (KNPub), 2026)
Forming the faith of children in the digital era demands a methodological transformation from the conventional lecture-based approach toward more visual and interactive methods. While various studies have examined visual media in faith education, research on the negotiation of the meaning of religious symbols within the context of local culture specifically Dayak culture remains limited. This study aims to analyze the implementation of visual-participatory catechesis based on YOUCAT for Kids within the Children’s Catholic Faith Formation Program at the Cathedral Parish of Saint Mary, Palangka Raya. The research employs a qualitative approach with a case study design and the photo-elicitation method, involving 14 informants consisting of Children’s Catholic Faith Formation children, the parish priest, the head of the evangelization ministry, catechists, and parents, and was conducted over a one-month period. Analysis is carried out using George Herbert Mead’s Symbolic Interactionism and James Fowler’s Theory of Faith Development to understand how children negotiate the meaning of Western religious symbols within the context of Dayak culture. The results show that the use of visual media significantly improves material retention and active participation among children. Furthermore, the study identifies a process of meaning negotiation when children interpret sacramental symbols through their local cultural experiences. This research proposes a five-stage catechetical model Observing, Listening, Dialoguing, Participating, and Living as a pastoral solution for the local Church in addressing the challenges of Generation Alpha. The study is limited to a single parish and a relatively short research duration, so the findings cannot yet be generalized to broader contexts.